Perianal Crohn's Disease is Associated with Distal Colonic Disease, Stricturing Disease Behavior, IBD-Associated Serologies and Genetic Variation in the JAK-STAT Pathway. Issue 4 (April 2016) - Kaur, Manreet; Panikkath, Deepa; Yan, Xiaofei; Liu, Zhenqiu; Berel, Dror; Li, Dalin; Vasiliauskas, Eric A.; Ippoliti, Andrew; Dubinsky, Marla; Shih, David Q.; Melmed, Gil Y.; Haritunians, Talin; et al.
Abstract : Background: Perianal Crohn's Disease (pCD) is a particularly severe phenotype associated with poor quality of life with a reported prevalence of 12%–40%. Previous studies investigating the etiology of pCD have been limited in the numbers of subjects and the intensity of genotyping. The aim of this study was to identify clinical, serological, and genetic factors associated with pCD. Methods: We performed a case–control study comparing patients with (pCD+) and without perianal (pCD − ) involvement in CD; defined as the presence of perianal abscesses or fistulae. Data on demographics and clinical features were obtained by chart review. Inflammatory bowel disease-related serology was determined by enzyme-linked immunosorbent assay. Genetic data were generated using Illumina genotyping platforms. Results: We included 1721 patients with CD of which 524 (30.4%) were pCD+ and 1197 were pPCD − . pCD was associated with distal colonic disease (Odds ratio 5.54 [3.23–9.52], P < 0.001), stricturing disease behavior (1.44 [1.14–1.81], P = 0.002) and family history of inflammatory bowel disease (4.98 [3.30–7.46], P < 0.001). pCD was associated with higher anti-sacharomyces cerevisae antibodies IgA ( P < 0.001) and OmpC ( P = 0.008) antibody levels. pCD was associated with known inflammatory bowel disease loci, including KIF3B, CRTC3, TRAF3IP2, JAZF1, NRIP1, MST1, FUT2, and PTGER (all P < 0.05). We also identified genetic association with genes involved in autophagy (DAPK1, P = 5.11 × 10 −5 ), TNF alpha pathways (NUCB2, P = 8.68 × 10 −5 ; DAPK1), IFNg pathways (DAPK1; NDFIP2, P = 8.74 × 10 −5 ), and extracellular matrix and scaffolding proteins (USH1C, P = 8.68 × 10 −5 ; NDFIP2; TMC07, P = 8.87 × 10 −5 ). Pathway analyses implicated the JAK-Stat pathway (pc = 3.72 × 10 −5 ). Conclusion: We have identified associations between pCD, more distal colonic inflammation, Crohn's disease-associated serologies, and genetic variation in the JAK-Stat pathway. Abstract : Supplemental Digital Content is Available in the Text.Article first published online 3 March 2016.